(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In spite of great progress in our modern era, personal problems have not been eliminated. In fact theorist such as form and Toffler suggest that our progress brings new and possibly more difficult, adjustment problems. The popularity of unorthodox religious groups and self-help represents two of the more interesting manifestations of our struggle to find a sense of direction in our confusing world. Psychology is the scientific study of behavior. Adjustment, Intelligence, Personality are a broad area of study in psychology that focuses on how people adapt effectively or ineffectively to the demands and pressures around them. These adoptions, adjustment efforts are greatly affected by personality and intelligence.